Dramas in de wolken: Luchtreizen en luchtreizigers : De Aarde en haar Volken, 1875 - Anonymous (Salt Lake City, UT : Project Gutenberg, 2004)
"Dramas in de wolken: Luchtreizen en luchtreizigers" by Anonymous is a historical account likely written in the late 19th century. The work examines the excitement and fervor surrounding the invention of hot air balloons, detailing the societal and scientific impacts of early aeronautics in the context of its historical significance and the public's reactions to these innovations. The opening of the text discusses the enthusiasm that the first air travel elicited, particularly in France during the late 18th century. It describes how the transformative nature of ballooning captivated imaginations, likening it to the discovery of America in its ability to stir public sentiment and pride. This fervor is juxtaposed against the reality that, despite the initial expectations, ballooning technology had made limited advancements in precision and control, leaving air travelers at the mercy of the winds. As the narrative progresses, it introduces notable figures involved in early aeronautics, setting the stage for discussions on their inventions and experiences in this captivating yet perilous new domain. (This is an automatically generated summary.)
Release date is 2004-11-27
Produced by Jeroen Hellingman and the PG Distributed Proofreaders Team
Keywords: Balloons